Political experience and the intersection between race and gender. (3rd April 2019) - Carey, Tony E.; Lizotte, Mary-Kate
ABSTRACT: Prior research has treated political experience as if it had similar effects for every candidate. However, recent studies suggest that the effects of political experience on trait judgments and candidate evaluations may vary depending on a candidate's demographic characteristics. Accordingly, this study investigates whether the influence of prior experience varies depending on the racial and gender background of political candidates. To explore this topic, we employ an experiment with a 2 (Race: White and Black) × 2 (Sex: Male and Female) × 2 (Experience: Experienced and Inexperienced) factorial design. The expectation is that political experience will have the greatest impact for white male candidates when compared to female and African American candidates. Furthermore, the study explores the differential effects of political experience by examining whether the influence of experience on competence ratings varies depending on the negative racial and gender attitudes of participants. The findings suggest that citizens are more inclined to distinguish between white male candidates across different levels of political experience, while they evaluate black and/or female candidates similarly, regardless of experience. Moreover, the evidence suggests that gender bias may explain why we observe the disparity between male and female candidates.